A Distributed Memory Parallel Fourth-Order IADEMF Algorithm - Mansor N.A.; Zulkifle A.K.; Alias N.; Hasan M.K. (Science and Information Organization, 2023)
Boundary conditions; Computer operating systems; Iterative methods; Distributed Memory; Distributed memory architecture; Fourth-order; Fourth-order method; Iterative alternating decomposition; Parallel performance; Parallel performance evaluation; Performances evaluation; Red-black; Red-black orderings; Memory architecture